PENATA LAKSANAAN PENYIMPANAN REKAM MEDIS DI PUSKESMAS PISANGAN - Indah Kristina; Ambarwati (APIKES Bhumi Husada Jakarta, 2022)
The implementation of Community Service activities at the Pisangan Health Center aims to assist the management of the health center's medical record storage, especially the shrinkage of medical records, carried out according to plan and running smoothly. This activity was carried out in collaboration with the Pisangan Health Center. Activities include observing the storage room, the number of shelves is sufficient to accommodate active medical records, there is no indication for storing medical records, there is no outguide, tracer, medical records with family folders, currently in the process of transitioning to individual folders. Medical records that have been destroyed have not yet been made. Minutes of the destruction have not been made. assistance in assessing 7039 family folder medical records and 3031 individual medical records still in the active medical record category. The recommendations submitted were making an official report on the destruction of medical records that had been destroyed, using the guidelines for managing medical record shrinkage at the Puskesmas, completing supporting equipment for storing medical records, rearranging the alignment of medical records using final numbers and placing medical records in sub shelves according to their capacity. Access to Medical Records repository. Keywords: management, storage, medical records